Banovinska konferenca Jugoslovanske nacionalne stranke leta 1937 v Ljubljani - Friš, Darko (Zgodovinski časopis, 2005)
The study deals with the most significant political activities in the Kingdom of Yugoslavia after the resignation of prime minister Bogoljub Jevtić in June 1935. Described is the relationship between the newly-organized ruling Yugoslav Radical Party (Jugoslovanska radikalna zajednica - JRZ), which consisted also of the supporters of the former Slovene People's Party (Slovenska ljudska stranka - SLS), and the Yugoslav National Party (Jugoslovanska nacionalna stranka - JNS) in the opposition. The study details and analyzes the events taking place during a regional conference organized by the Yugoslav National Party in Ljubljana in June 1937, and the response of Slovene newspapers to these events, the response fully reflects the relation between the supporters of the politics of Yugoslav nationalists and their apposition.
Keywords: politična zgodovina; politične stranke; political party; Kingdom of Yugoslavia; Kraljevina Jugoslavija; zgodovinski pregledi